2020
DOI: 10.3390/rs12182934
|View full text |Cite
|
Sign up to set email alerts
|

Forest and Crop Leaf Area Index Estimation Using Remote Sensing: Research Trends and Future Directions

Abstract: Leaf area index (LAI) is an important vegetation leaf structure parameter in forest and agricultural ecosystems. Remote sensing techniques can provide an effective alternative to field-based observation of LAI. Differences in canopy structure result in different sensor types (active or passive), platforms (terrestrial, airborne, or satellite), and models being appropriate for the LAI estimation of forest and agricultural systems. This study reviews the application of remote sensing-based approaches across diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 222 publications
0
12
0
Order By: Relevance
“…The accuracy of estimates using VIs as model inputs can be affected if the study does not identify an appropriate index through model inversion [64]. Further information about this technique presenting the general concept of VIs can be found in these studies: [65][66][67] for LAI, ref. [68] for fCover, and [69] for CC.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…The accuracy of estimates using VIs as model inputs can be affected if the study does not identify an appropriate index through model inversion [64]. Further information about this technique presenting the general concept of VIs can be found in these studies: [65][66][67] for LAI, ref. [68] for fCover, and [69] for CC.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…There are several review research studies on LAI estimation using remote sensing [47][48][49][50][51][52]. These studies show the importance, limitations, and strategies to improve the accuracy of each of these methods [49,[53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…These studies show the importance, limitations, and strategies to improve the accuracy of each of these methods [49,[53][54][55]. Most of these studies focused on forest cover, and very few reviewed the existing LAI estimation methods for cropland using optical remote sensing including multispectral, hyperspectral and LiDAR [47,52]. All of the existing studies focused on reviewing existing studies and underscoring the advantages and limitations of current approaches.…”
Section: Introductionmentioning
confidence: 99%
“…When considering other photosynthetically-active plant parts besides the leaves, it is called the green area index or plant area index [ 8 ]. Crop LAI estimation using RS reflectance data and empirical modelling approaches (both parametric and non-parametric) have shown promising results, but also considerable variation in prediction quality (coefficient of determination (R 2 ) ranges from 0.36 to 0.97) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, RS data application has not been examined for crops like finger millet and lablab, which are major monsoon crops in the tropical region (e.g., Bengaluru, Southern India). Furthermore, few studies have compared different remote sensing platforms (e.g., in-situ vs airborne vs spaceborne) and sensors (multispectral vs hyperspectral) for crop vegetation parameters estimation [ 16 , 28 ]. Thus, this study sought to fill the identified research and knowledge gap for RS for monsoon crop monitoring.…”
Section: Introductionmentioning
confidence: 99%